A field test of the use of pop‐off data storage tags in freshwater fishes. Issue 6 (12th October 2017) - Raby, G. D.; Johnson, T. B.; Kessel, S. T.; Stewart, T. J.; Fisk, A. T.
Abstract : In the present study, pop‐off data storage tags (pDST) without any transmitting capabilities were attached to 118 adult salmonids in a 19 000 km 2 freshwater system (Lake Ontario). The 9·3 cm long cylindrical tags were externally attached to fishes using a backpack‐style harness, set to record pressure (dBar ≈ depth in m) and temperature every 70 s (and at some key times, every 5 s) and programmed to release from the harness and float to the surface after c . 1 year. Recapture of the bright‐orange tags for data retrieval relied on members of the public finding tags on shore, or on anglers capturing fishes with tags attached and using the contact information displayed on each tag to mail tags to the research team in exchange for a monetary reward. Thirty‐seven tags were found and returned from the 118 released (31%), while 26 of the 118 tags (22%) remained scheduled to pop‐off in summer 2017. Of the 37 tags returned, 23 were from wild‐caught fishes (out of 88 wild‐caught and tagged fishes; 26%) and yielded useful data whereas 14 were from hatchery‐reared fishes that were opportunistically tagged and appear to have been unable to acclimate to life in the wild and died days to weeks after release. The field study described here thus demonstrated that pDSTs can be a viable option for collecting large amounts of high‐resolution depth and temperature data for salmonids in freshwater systems. Technical challenges, limitations and unknowns related to the use of pDSTs with freshwater fishes are discussed. In addition, pDSTs are compared with alternate electronic tagging technologies and assessed for their potential as a more widespread tool in research on freshwater fishes.